Indoor radon in Spanish workplaces. A pilot study before the introduction of the European Directive 2013/59/Euratom - Alberto Ruano-Ravina; Claudia Narocki; María José López-Jacob; Ana García Oliver; María de la Cruz Calle Tierno; Joaquín Peón-González; Juan Miguel Barros-Dios (Elsevier, 2019)
Objective: To explore whether there is a possible problem regarding indoor radon concentration surpassing the new European Directive 2013/59/Euratom threshold in Spanish workplaces. We also aim to find out whether radon concentration might be associated with certain characteristics of workplaces. Method: We performed a cross-sectional study to measure indoor radon concentrations in Spanish workplaces including five different sectors (education, public administration, the health sector, the tourist sector and the private sector). To be measured, the workplace should be occupied permanently by at least one worker. Alpha-track type radon detectors were placed for at least three months and read at the Galician Radon Laboratory at the University of Santiago de Compostela. A descriptive analysis was performed on radon distribution by sector, building characteristics and number of workers affected. Results: We faced enormous difficulties in finding volunteers for this study. Galicia and Madrid had the highest number of measurements. Of a total of 248 measurements, 27% had concentrations above 300 Bq/m3. Median radon concentration was 251 Bq/m3 in Galicia, followed by Madrid, with 61.5 Bq/m3. Forty-six percent of the workplaces measured in Galicia had radon concentrations higher than 300 Bq/m3 followed by 10.6% in Madrid. Nineteen percent of all workers were exposed to more than 300 Bq/m3 and 6.3% were exposed to radon concentrations higher than 500 Bq/m3. Conclusion: Indoor radon exposure might be a relevant problem in Spanish workplaces and the number of affected workers could be high. The prevalence of workers exposed to high radon concentrations probably depends on the geographical area. Resumen: Objetivo: Explorar si podría existir un problema en cuanto a la concentración de radón en los puestos de trabajo en España por superación del umbral propuesto por la nueva Directiva Europea 2013/59/Euratom. También se pretende conocer si la concentración de radón puede estar asociada a las características de los puestos de trabajo. Método: Estudio transversal en seis regiones y diferentes sectores (educación, administración pública, sanitario, turístico y privado). El puesto de trabajo medido debía ser ocupado de manera permanente por al menos un trabajador. Los detectores de radón de tipo alfa-track estuvieron colocados al menos 3 meses y fueron revelados en el Laboratorio de Radón de Galicia, de la Universidad de Santiago de Compostela. Se realizó un análisis descriptivo de la concentración de radón por sector, por características de los edificios y por número de trabajadores afectados. Resultados: Hubo dificultades para encontrar voluntarios para este estudio. Galicia y Madrid tuvieron el mayor número de mediciones. Se midieron 248 lugares de trabajo, con el 27% por encima de los 300 Bq/m3. La concentración mediana fue de 251 Bq/m3 en Galicia, seguida de Madrid con 61,5 Bq/m3. El 46% de los puestos de trabajo en Galicia tenían concentraciones mayores de 300 Bq/m3, y el 10,6% en Madrid. El 19% de los trabajadores estuvieron expuestos a más de 300 Bq/m3 y el 6,3% a más de 500 Bq/m3. Conclusión: La exposición a radón podría ser un problema de salud relevante en los lugares de trabajo en España. El número de trabajadores expuestos parece elevado. La prevalencia de trabajadores afectados depende del área geográfica. Keywords: Radon, Lung cancer, Cross-sectional studies, Workplace, Spain, Palabras clave: Radón, Cáncer de pulmón, Estudio transversal, Lugar de trabajo, España